2020
DOI: 10.3892/mco.2020.2019
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal teratoma misdiagnosed as a gastric stromal tumor: A case report

Abstract: The misdiagnosis of retroperitoneal teratoma as a gastric stromal tumor is rarely reported. There are numerous abdominal organs, and retroperitoneal tumors are easily concealed by organs situated more anteriorly on the abdomen; therefore, retroperitoneal tumors are easily misdiagnosed as human digestive system tumors by abdominal surgeons. We herein present the case of a 39-year-old female patient who was diagnosed with a gastric stromal tumor (GST) on preoperative examination, whereas the postoperative diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It is worth mentioning that the tumor was located in the retroperitoneal space, between the aorta and the lesser gastric curvature. The histopathological examination showed that the tumor, which was initially thought to be a stromal gastric tumor, was in fact a retroperitoneal teratoma (47).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the tumor was located in the retroperitoneal space, between the aorta and the lesser gastric curvature. The histopathological examination showed that the tumor, which was initially thought to be a stromal gastric tumor, was in fact a retroperitoneal teratoma (47).…”
Section: Discussionmentioning
confidence: 99%